Legal Certainty of Filing Judicial Review in Tax Dispute Resolution After the Constitutional Court Decision No. 24/PUU-XXI/2024 - Listanti, Vidyatika Dwi (CV. Publikasi Indonesia, 2025)
Judicial review plays a crucial role in ensuring justice and legal certainty in tax dispute resolution, particularly in Indonesia, which adheres to the principle of a rule of law (Recht Staat). The Constitutional Court Decision No. 24/PUU-XXI/2024, however, limits the Directorate General of Taxes from filing judicial reviews, creating challenges for addressing errors in tax dispute decisions. This research uses a normative juridical approach to analyze the legal implications of this restriction, examining its impact on state revenue and legal fairness. Findings indicate that such limitations not only reduce legal certainty but also hinder the correction of judicial errors, potentially causing state financial losses. To address these issues, the study recommends a regulatory model that balances the rights of both taxpayers and tax authorities, fostering fair legal certainty and supporting tax revenue optimization for the State Budget. This regulatory refinement is vital for maintaining justice and fiscal stability in Indonesia.